A case of placental site trophoblastic tumor complicating nephrotic syndrome in which hysteroscopic biopsy did not yield a definitive diagnosis - Wataru Sato; Yasuko Miura; Hiromitsu Shirasawa; Yukiyo Kumazawa; Jin Kumagai; Yukihiro Terada (Wolters Kluwer Medknow Publications, 2017)
Placental site trophoblastic tumor (PSTT) is the rarest subtype of gestational trophoblastic neoplasm. We present a case of PSTT complicating nephrotic syndrome. A 32-year-old woman experienced irregular menstrual bleeding and lower extremity edema 18 months after delivery. She was diagnosed with nephrotic syndrome and exaggerated placental site based on the hysteroscopic biopsy results. During follow-up, transvaginal color Doppler ultrasound showed an enlarged uterus filled with a hypervascular mass. Positron emission tomography-computed tomography showed diffuse accumulation in the entire uterus. The patient was diagnosed with PSTT only after total hysterectomy. Postoperatively, serum β-human chorionic gonadotropin decreased to within the normal range and her nephrotic syndrome resolved. She has remained without evidence of recurrence for 15 months. It is difficult to diagnose PSTT definitively. Most patients with PSTT are of reproductive age, therefore, to maintain fecundity, therapy development is expected.